Drastic Alteration of Ribosomal RNA and Ribosomal Proteins in Showdomycin-Resistant Escherichia coli - Beljanski, Mirko (1971)
In a mutant of Escherichia coli resistant to showdomycin, both the 50S and 30S ribosomal subunits contain RNA species in which the purine concentration greatly exceeds that of pyrimidines. The same is true for total rapidly-labeled RNA. The modified ribosomal RNA hybridizes poorly with homologous DNA, which is apparently unchanged in base composition. Acrylamide gel electrophoresis of mutant ribosomal proteins shows a highly altered protein pattern for both ribosomal subunits, although the activity of these ribosomes is not decreased.